The effects of ethanolic extract of green algae (ulva lactuca l.) on blood cholesterol levels in male rats induced by a high fat diet - Wahyu Widyaningsih; Nina Salamah; Fella Qulsum Maulida (Faculty of Medicine, Universitas Islam Indonesia, 2016)
Background : Nowadays, cardiovascular disease is increasing in number each year. It is triggered by high cholesterol diet consumed by urban people. Green algae (Ulva lactuca L.) contains phytomelatonin levels that can ease cholesterol. Objective : To know about the effect of giving green algae ethanolic extract in male strain Wistar mice's cholesterol level. Methods : This research involved 36 male strain Wistar mice divided to six groups. Negative control injected with 2 ml/200 gBW lard, positive control injected with 0,18 mg/200 gBW simvastatin and lard, group III, V, V each given lard and injected with ethanolic extract of green algae at a dose of 50 mg/kgBW, 100 mg/kgBW and 200 mg/kgBW respectively, and normal control given AD 2 dietary treatment. Each group was given the same treatment peroral in 56 days and the blood was taken every 14 days through sinus orbitalis. The blood cholesterol level was analyzed by using enzymatic CHOD-PAP method. Data obtained were statistically examined using Two way ANOVA , Kolmogorov Smirnov, Levene's method and LSD with confidence level at 95%. Results : The blood cholesterol level were not significanly different between the negative and normal control. The result of cholesterol level for 14, 28, and 42 days for all group did not increase compared to negative control, but cholesterol level in group with 200 mg/kgBW dose extract indicated significant difference with negative control for 56 day. Conclusion : Giving ethanolic extract of green algae for 56 days decreased blood cholesterol level in male rats.